Proceedings of the International Conference on Compilers, Architecture, and Synthesis for Embedded Systems - CASES '01 2001
DOI: 10.1145/502217.502253
|View full text |Cite
|
Sign up to set email alerts
|

The performance and energy consumption of three embedded real-time operating systems

Abstract: This paper presents the modeling of embedded systems with SimBed, an execution-driven simulation testbed that measures the execution behavior and power consumption of embedded applications and RTOSs by executing them on an accurate architectural model of a microcontroller with simulated real-time stimuli. We briefly describe the simulation environment and present a study that compares three RTOSs: µC/OS-II, a popular public-domain embedded real-time operating system; Echidna, a sophisticated, industrial-streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 30 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…In the past, the energy behavior of embedded and real-time operating systems has been evaluated [8,2,27]. In [9], a fullsystem energy-aware simulator is developed and the necessity of simulating OS energy is quantified.…”
Section: Figure 1 % Of Energy Dissipated By the Os On The Experimentmentioning
confidence: 99%
“…In the past, the energy behavior of embedded and real-time operating systems has been evaluated [8,2,27]. In [9], a fullsystem energy-aware simulator is developed and the necessity of simulating OS energy is quantified.…”
Section: Figure 1 % Of Energy Dissipated By the Os On The Experimentmentioning
confidence: 99%
“…Li et al [2001] presented issues concerning the implementation of a low power OS and demonstrated the energy advantage of the event-driven TinyOS over a general-purpose OS (eCos). Baynes et al [2001] compared the energy consumption of three real-time OSs on a Motorola M•CORE processor [Motorola Inc. 1998].…”
Section: Related Workmentioning
confidence: 99%
“…Recently, the energy behavior of embedded, realtime operating systems has been studied in [15,16]. In [7], a fullsystem energy simulator is developed and the necessity of simulating OS energy is quantified.…”
Section: Related Workmentioning
confidence: 99%